Students’ Performance in Writing English Exposition Text of the Eleventh Graders of SMAN 13 Jakarta - Katarina Kriheni Wijayanti; Sudarya Permana (Stairs, 2020)
This article analyzed the understanding of eleventh graders' students at SMAN 13 Jakarta regarding the exposition text. The purpose of this paper was to find out to what extent the comprehension of eleventh graders of students of exposition text through the levels in the Blake Education rubric. The analysis table developed by Blake Education (1998) was used for the essay text analysis process. From the four main indicators studied, the results of this study indicated that (1) the average student was already at level 2, which could be categorized as an understanding of the exposition text; (2) although the average in both the Natural Sciences Program and Social Sciences Program was at level 2, the data showed that the students of Natural Science Program understood the exposition text better than the students of Social Science Program did. This paper also provided evidence regarding the difficulties of students in writing exposition texts. These findings showed that the ability of students to write exposition texts was in the middle or average level.